THE ROLE OF SELF-EFFICACY IN WRITING ACHIEVEMENT OF INDONESIAN SENIOR HIGH SCHOOL STUDENTS - Asmaul Husna; Ary Setya Budhi Ningrum; Galuh Nur Rohmah (Edulingua: Jurnal Linguistiks Terapan dan Pendidikan Bahasa Inggris, 2021)
Writing is one of productive skills in English learning. This activity can be influenced by another psychological factor such as self-efficacy. It is a psychological factor that is related to someone belief in doing something successfully. This research aims at investigating the correlation between self-efficacy and writing achievement. This research uses correlation quantitative as the research design. The participants are 110 students of the tenth grade students of MAN 1 Kota Kediri. To get data, the instruments used are self-efficacy questionnaire and writing test. The result of this research revealed that there is no significant correlation between self-efficacy and writing achievement.